Corrosion resistance of NiTi shape memory alloy after hybrid surface treatment using low-temperature plasma. (March 2017) - Witkowska, Justyna; Kamiński, Janusz; Płociński, Tomasz; Tarnowski, Michał; Wierzchoń, Tadeusz
Abstract: This article presents a study of the structure, surface roughness and corrosion resistance of composite layers consisting of a layer of Ti(ON) titanium oxynitride with a surface zone of amorphous carbon modified with nitrogen and hydrogen. They were produced on NiTi alloy in a hybrid process combining oxidation in low-temperature plasma and Radio Frequency Chemical Vapor Deposition process (RFCVD). Ti(ON)+a-CNH type composite layers can be produced in temperatures below 300 °C, i.e. in conditions ensuring that the specific properties of NiTi alloys, namely shape memory and superelasticity, are maintained. They provide a significant increase in corrosion resistance and may be produced on specimens having complex shapes, which is of great importance in the case of possible application as medical implants. Highlights: Combination of plasma oxidizing of NiTi shape memory alloy and RFCVD is presented. Structure of surface composite layers a-CNH + Ti(ON) type is described. Titanium oxinitride layer has nanocrystalline structure. a-CNH + Ti(ON) composite layers increase the corrosion resistance of NiTi alloy.